Non-coliform aerobic bacterial contaminants of drinking water in Capri, Novaliches; Bagong-Ilog, Pasig; and Marulas, Valenzuela, Metro Manila. - Florentin, Magdalena L. (1983)
36 water samples were collected from 3 areas in Metro Manila, namely: Capri, Novaliches; Bagong-Ilog, Pasig; and Marulas, Valenzuela. 7 of these were obtained from public sources and 29 from private households. The non-coliform bacteria that were isolated from these samples include Acinetobacter anitratum, Acinetobacter lwoffi, Pseudomonas species, Alkaligenes fecalis, Proteus species, Citrobacter species, Bacillus subtilis, Staphylococcus aureus and the unclassified bacteria, which cannot be identified by the procedures used in this study. A. anitratum and A lwoffi were isolated in high frequency, i.e., 41.67 and 61.11 , respectively, from the 36 samples. The water samples also contained coliforms, namely, Escherichia coli, Enterobacter species and Klebsiella pneumoniae. Only 28.57 of the 7 samples collected from public sources contained coliforms while 89.66 of the samples from the private sources were positive for coliforms. The standard palte counts of the 36 water samples showed that 77.78 had a count of 500 organisms/ml. Of the 29 samples obtained from private sources, 93.10 showed counts of 500/ml and only 14.29 of the 7 samples obtained from the public sources gave similar counts. 20 of the 35 representative isolates tested for enterotoxigenicity using rat intestinal loop test were positive for enterotoxin production. These were: 1 E. coli, 1 A. anitratum, 2 Pseudomonas species, 2 Citrobacter species and 1 S. aureus. The results of this study showed that the water samples obtained from public sources generally contain lesser number of bacteria, i.e., they are less contaminated than that of the private sources. The enterotoxigenecity test result, which probably the 1st report of this kind locally, suggests that the noncoliform bacteria isolated from the water samples which are considered nonpathogen of the gastrointestinal tract are potential causes of gastroenteritis.
Thesis (MS Public Health, Medical Microbiology)--University of the Philippines Manila.
Keywords: Water -- Microbiology; Non-coliform bacteria; Bacteria, aerobic